HUBUNGAN RIWAYAT POLA PEMBERIAN ASI, JENIS MPASI DAN PENGETAHUAN IBU TERHADAP STATUS GIZI (BB/U) USIA 6-24 BULAN DI WILAYAH SAWANGAN DAN LIMO KOTA DEPOK - Khansa Zahra Savira (2023)
Globally, malnutrition causes 45% of total child deaths which shows the importance of a good diet to reduce malnutrition problems. The child's diet begins with a history of exclusive breastfeeding followed by the provision of complementary foods, either local or manufactured complementary foods. Feeding patterns must also be accompanied by a good level of maternal knowledge to realize the normal nutritional status of the child. The purpose of this study was to determine the relationship between the history of exclusive breastfeeding, the type of complementary food and the level of knowledge of mothers with the nutritional status of children 6-24 months. The study used an analytical survey method with a Cross Sectional approach. Determination of sample size using cluster sampling technique. Data collection was carried out by interviewing respondents, namely mothers who have children aged 6-24 months. The independent variables in this study were the history of breastfeeding patterns, the type of complementary food, the level of knowledge of the mother whereas, for the dependent variable was the nutritional status of children aged 6-24 months. The results of the bivariate test with chi-square found that the history of breastfeeding patterns was not related to the nutritional status (BB / U) of children aged 6-24 months (p-value = 0.877), the type of complementary food was not related to the nutritional status (BB / U) of children aged 6-24 months (p-value = 0.118) whereas, the level of maternal knowledge showed a relationship with the nutritional status (BB / U) of children aged 6-24 months (p = 0.011). It is expected that the community will always pay attention to the nutritional status of children.